Pelaksanaan Kegiatan Pengabdian Masyarakat di Rumah Quran Aisyah Radhiallahu anha Desa Bangun Sari, Tanjung Morawa Ramadhan 1442 H, 2021 M. - Fakhrurrozi Fakhrurrozi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
Community service activities held at Rumah Quran Aisyah Radhiallahu anha call and invite the souls of daa'iyah who should be present in every Muslimah. The student of KKL STAI As-Sunnah named this service program with “wardah” (color the Ramadan with blessings) which is adapted to the nuances of the holy month Ramadan. This year, Rumah Quran held a program with the theme of "kurma" (achieve Ramadan with the Qur'an), which is an activity to memorize one juz of the Al-Qur’an on 25 days and it’s only devoted to women and children. This program is divided into two categories; offline and online. The purpose of this activity is to increase Muslimah’s enthusiasm in achieving the greatness of the Al-Qur'an in Ramadan, and also to be able to manage their time in this holy month. In addition to the Al-Qur'an memorization program activities, there is also a daurah "Tazkiyatun Nafs" on every Friday via WhatsApp group, Live Streaming on Facebook and Instagram. Supporting activities in this Ramadan program is "memorizing the hadith of al-Arba'in an-Nawawiyah" which is held by online and many conversations for children. For other additional online activities, the student of Kkl STAI As-Sunnah hold a daurah women's fiqh study on weekends via zoom. Students of STAI As-Sunnah participated to success this entire program by becoming the organizing committee. As the closing of all activities, there was a competition for hifdzil Qur'an, hifdzil hadith, and breaking the fast with the offline "kurma" participants.